Diameter-Dependent Shape Memory Effect and Superelasticity in Ni-Mn-Ga Alloy Micro-fibers (Journal of Solar Energy Research Updates, 2023)
Abstract: The functional properties of shape memory alloys (SMAs) may be affected by the material size and thus is important for designing micron-sized devices. Here the diameter-dependent size effect was demonstrated in Ni-Mn-Ga fibers with diameters of 15, 41, 53 and 70μm. The effect of fiber diameter on the shape memory effect (SME) and superelasticity (SE) was systematically studied. The results showed that all Ni-Mn-Ga fibers exhibited good stress assisted thermal cycles and SE, both diameter-dependent. For stress assisted thermal cycles, the temperature hysteresis of martensite transformation (MT) and sensitivity of MT temperature vs stress increased with increasing fiber diameter. While for SE, the stress hysteresis, temperature dependence of critical stress and energy dissipation capacity decreased with increasing fiber diameter. Thermodynamic analysis revealed that the diameter-dependent effect may be attributed to the different heat exchange and frictional work dissipation capacities related to the specific surface areas that affected the thermal- or stress-induced MT processes. Such diameter dependence in Ni-Mn-Ga micro-fibers needs to be considered for the design and application in micro-sized devices.